ECONOMIC GROWTH AND COHESION IN THE EUROPEAN UNION - HOLOBIUC ANA-MARIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
Since the first initiatives of regional integration in the 20th century, the European group has gone through important stages, evolving from customs union to economic and monetary union. During this time, the challenges for the European group have not diminished. By contrary, the internal vulnerabilities were enhanced by the aggressive crises that affected in the last decades the entire World. Despite the transformations of the European Union, cohesion has always remained a main objective of the group, with the purpose to promote the unity between Members. Considering this fundamental principle of the European Union, the aim of this paper was to determine the convergence patterns, together with the main determinants of prosperity in the interval 2000 and 2022. Focusing on absolute βconvergence, we have initially determined the relationship between the initial level of GDP per capita and the average growth rates based on cross-sectional data. We have concluded that the initially less developed countries tend to experience higher growth rates compared to the developed Members. Moreover, the study suggests that the average convergence speed in the European Union was around 2% per year. Complementarily, using panel regressions to estimate conditional β-convergence, we have illustrated that factors such as investment, exports of goods and services and inflation had a positive impact on the dynamics of GDP per capita. Consequently, strengthening the macroeconomic policy framework has generated prosperity gains for the European Union.